Reproductive planning in Indigenous area and the search for differentiated care: the dilemmas between inequality and difference - Ávila, Bruna Teixeira; Alves, Sandra Valongueiro (Saúde e Sociedade, 2022)
Differentiated care is a fundamental principle for a non-colonizing care of the Indigenous populations. One of the challenges within this field is reproductive planning since it involves tensions between collective and individual wills, as well as between authority and autonomy, especially with the more continuous insertion of professionals with the Programa Mais Médicos (More Doctor Program), as occurred in the Yanomami Territory. This article aims to discuss the aspects involved in a differentiated care regarding reproductive planning by comparing the work of health professionals in Indigenous and non-Indigenous areas. Thus, an ethnographic case study was conducted based on participant observation of the teams’ practice, accessed via the Programa Mais Médicos Supervision, and interviews with six professionals, selected for the diversity of their profile. From the content analysis, three categories were identified: difference and inequality, similarities, and challenges. These divisions allows for the notion of physiological comparison, which generates a biomedical approach, encompassing the confusion between difference and inequality, the aspect responsible for favoring colonization and the denial of rights – and even the understandings of professionals about the culture – which permeates the intercultural dialogue.